Acute Effects of Supra- and High-Loaded Front Squats on Mechanical Properties of Lower-Limb Muscles - Krzysztofik, Michal; Wilk, Michal; Kolinger, Dominik; Pisz, Anna; Świtała, Katarzyna; Petruzela, Jan; Stastny, Petr (Sports, 2023)
Knowledge about the acute effects of supramaximal-loaded resistance exercises on muscle mechanical properties is scarce. Therefore, this study aimed to examine changes in dominant limb biceps femoris and vastus lateralis oscillation frequency and stiffness before and after high- and supramaximal-loaded front squats. Nineteen male handball players participated in the experimental session with a barbell front squat 1RM. The first set was performed at 70% of the 1RM for four repetitions, and the second and third sets were performed at 90%1RM in an eccentric-concentric or an eccentric-only manner at 120% of the 1RM for three repetitions. The handheld myometer was used for the measurement of the biceps femoris and vastus lateralis stiffness and the oscillation frequency of the dominant limb 5 min before and at the 5th and 10th min after front squats. A two-way ANOVA neither indicated a statistically significant interaction (p = 0.335; η2 = 0.059 and p = 0.103; η2 = 0.118), the main effect of a condition (p = 0.124; η2 = 0.126 and p = 0.197; η2 = 0.091), nor the main effect of the time point (p = 0.314; η2 = 0.06 and p = 0.196; η2 = 0.089) for vastus lateralis and biceps femoris stiffness. However, there was a statistically significant interaction (F = 3.516; p = 0.04; η2 = 0.163) for vastus lateralis oscillation frequency. The post hoc analysis showed a significantly higher vastus lateralis oscillation frequency at POST (p = 0.037; d = 0.29) and POST_10 (p = 0.02; d = 0.29) compared to PRE during the SUPRA condition. Moreover, Friedman's test indicated statistically significant differences in biceps femoris oscillation frequency (test = 15.482; p = 0.008; Kendall's W = 0.163). Pairwise comparison showed a significantly lower biceps femoris oscillation frequency in POST (p = 0.042; d = 0.31) and POST_10 (p = 0.015; d = 0.2) during the HIGH condition compared to that in the corresponding time points during the SUPRA condition. The results of this study indicate that the SUPRA front squats, compared to the high-loaded ones, cause a significant increase in biceps femoris and vastus lateralis oscillation frequency.